PENGARUH PROGRAM PENGELOLAAN SUMBERDAYA HUTAN BERSAMA MASYARAKAT (PHBM) TERHADAP PENDAPATAN PETANI PESANGGEM DI DESA SUKOWIDI KECAMATAN PANEKAN KABUPATEN MAGETAN - Desy Ardiaty Wahyuni (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2013)
This study aimed  to determine  the effect of Management   of Forest  Resources With Society  (PHBM) program's,  especially  PHBM land's  on income of pesanggem  farmers in Sukowidi  Village  Sub Panekan  Magetan  District.  Determination   of the sample  in this study using  purposive  random  sampling  which  is based on characteristics   the Institute of The Forest  Village  Community  (LMDH)  Lawu  Suko Lestari  in Sukowidi  Village Sub  Panekan  Magetan   District.  The  study  using  a sample  of 55 people.  The  data  was collected   by  questionnaire,     interview   and  documentation.    In  analyzing   the data  used statistical  method  with linier regression  test and correlation  product  moment  test. Based on  the  results  of data  processing     and  simultaneous   testing  on  significance   level  5% shows  that land area of PHBM   significant  effect on tile income of pesanggem  farmers  in Sukowidi Village Sub Panekan Magetan District.  it is seen from the value of Fhitung (110,079) >= Ftabel (4,02). The influence  of variables  Management  of Forest  Resources  With Society (PHBM)  program's,   especially  PHBM  land's  on income  of pesanggem  fanners  it shows with R Square  = 0,822 it is means  that income  influenced  by land area 67,56%  and while the remaining   32,44%  is intluenced  by other factors. While  results of the T test variable of Management  of Forest Resources  With Society  (PHBM)  program's,  especially  PHBM land's  is partiaUy significant  effect on income  of pesanggem  farmers  in Sukowidi  Village Sub Panekan  Magetan  District.  where  variable  the land area of PHBM thitung (10,492)  >= ttabel (1,673).